Pengaruh Core Stability Exercise Terhadap Peningkatan Aktivitas Fungsional Pada Low Back Pain Non-Spesifik - Ulfah Nidaussolihah; Afif Ghufroni; Pajar Haryatno (Jurusan Fisioterapi Poltekkes Kemenkes Surakarta, 2024)
Background: Non-specific low back pain is a complaints of pain that occurs in the lower back for which the cause is not clearly known. Core stability exercise is an exercise to activate the core muscles which can increase spinal stabilization and increase muscle strength so that functional activity increases. Objective: This study aims to determine the effect of providing core stability exercise on increasing functional activity in sufferers of non-specific low back pain. Method: The design of this research is one group pre and post-test with control. This research was conducted 3 times a week for 4 weeks with the sample being workers at PT. Iskandartext Solo which has met the inclusion criteria. In this study, it will be grouped into two groups with the measuring instrument used, namely the Oswestry disability index (ODI). Results: The average ODI value before and after treatment was 25.47 and 18.80 and the results of statistical tests using the paired t test showed p=0.000 (p<0.05), this shows that there is an effect of providing core stability exercise on increase in functional activity. Conclusion: There is the influence of givingcore stability exercise towards increasing functional activity in suffererslow back pain non-specific.